Corrigendum to “Evaluation of water absorption and chloride ion penetration of rice straw ash and microsilica admixed pavement quality concrete” - Pandey, Arunabh; Kumar, Brind (Elsevier Ltd, 2019)
In the original published version of this article, an error was present in "Table 1: Phase composition of cement, rice straw ash and microsilica". The values pertaining to percentage amount of SiO2, CaO and MgO in cement were incorrect. The correct values are 20.34, 62.16 and 0.79 respectively. The authors apologize for the mistake. A corrected Table 1 is displayed below. This correction does not, in any way, compromise the findings of the study, either in terms of the methodology, results, or interpretations drawn from the data therein. Both the HTML and PDF versions of the article have been updated to correct the error
Keywords: Evaluation of water absorption; Chloride ion penetration; Rice straw ash; Microsilica admixed pavement quality concrete